The reduction of NO[sub x] by HNCO. [RAPRENOx process] - Brown, N. J.; Garay, J. (Lawrence Berkeley Laboratory, 1992)
A chemical mechanism for the reduction of NO[sub x] by HNCO has been constructed to model NO[sub x] reduction in exhausts typical of natural gas combustion with the addition of radical boosters (fuel). Variables considered were the initial concentrations of NO, NO[sub 2], CO, O[sub 2], CH[sub 4], H[sub 2], and HNCO as well as initial temperatures. The chemical model was validated by comparing results with earlier model calculations of Miller and Bowman and with the experiments of Caton and Siebers and Lyon and Cole. Agreement with experiments was satisfactory. The reduction chemistry must be preceded by thermal ignition chemistry which generates radicals. The lowest temperature for which ignition occurs is the optimum temperature for reduction and defines the beginning of the temperature window. Reduction was not achieved for the natural gas exhaust'' for a reasonable residence time. Additional H[sub 2] added to the exhaust mixture enhanced reduction, but the addition of CO and CH[sub 4] did not. Under some conditions the computed sensitivity coefficient for nitrogen species and temperature exhibited self-similarity. Four reaction paths were identified which controlled the fate of the NO: the conversion of NO to NO[sub 2] via HO[sub 2], the conversion of NO[sub 2] to NO via reaction with H or O, the reduction of NO via NCO, and the reduction of NO from reactions with NH[sub i] species. The relative importance of the four was determined by the initial conditions.